Preparedness Level of Christian Polytechnic Institute of Catanduanes (CPIC) in Typhoon and Calamities in the Province of Catanduanes: Baseline for Curriculum Integration - Camonias, Robert (JPAIR Multidisciplinary Research, 2026)
This study assessed the disaster preparedness level of the Christian Polytechnic Institute of Catanduanes (CPIC) in terms of knowledge, risk perception, and cue to action among instructors and students, serving as the basis for developing a Curriculum-Integrated Comprehensive Emergency Plan (CICEP). Using a descriptive–comparative quantitative design, the study involved 20 instructors and 435 students selected through total enumeration and Slovin’s formula. Findings revealed that the institution demonstrated a Prepared level of disaster readiness across the three indicators, reflecting a moderate level of preparedness among the respondents. The school community showed adequate awareness of disaster risks and appropriate response actions, though areas such as leadership roles, communication flow, and evacuation planning required strengthening. A significant difference was identified in risk perception, with instructors exhibiting higher awareness due to training and experience, while no significant differences were observed in knowledge and cue to action. The results underscore the importance of continuous disaster education, participatory drills, and strengthened coordination mechanisms. The developed Curriculum-Integrated Comprehensive Emergency Plan (CICEP) institutionalizes disaster preparedness within academic instruction and operational systems, promoting sustained safety, collaboration, and resilience in the campus community.